Crisis liquidity facilities with nonbank counterparties: Lessons from the term Asset-Backed Securities Loan Facility - Ralf R. Meisenzahl; Karen M. Pence (Federal Reserve Bank of Chicago, 2022)
The Term Asset-Backed Securities Loan Facility (TALF), which addressed strains in the asset-backed securities market, was an unusual crisis facility because it provided loans to a wide range of nonbank financial institutions. Using new, detailed loan-level data, we study whether institutional differences across nonbanks affected nonbanks' support for key program goals-stabilizing markets quickly, winding down the program when conditions normalized, providing liquidity to a wide range of assets, and internalizing credit risk rather than shifting it to the government. As the program terms were the same for all TALF borrowers, our study can examine the role of institutional constraints.
Keywords: E52; E58; G12; G23; 330; Nonbank Financial Institutions; Securitization; Lender of Last Resort; Term Asset-Backed Securities Loan Facility; TALF